Factors influencing the financial performance of selected Islamic Banks in Malaysia and Indonesia / Fitrah Rahmatika Muslih - Fitrah Rahmatika , Muslih (2023)
These days, banking industry mostly uses a dual system, conventional banking and Islamic banking. Although Islamic banking is still relatively new compared to conventional banks, Islamic banking is recently growing rapidly throughout the world. In particularly, Malaysia and Indonesia are two countries with high development of Islamic banking compared to other countries in ASEAN. In fact, Malaysia and Indonesia were ranked as the first and the second out of 50 countries on the Islamic Finance Country Index (IFCI) in 2020. Therefore, this study was conducted to compare the factors that influence the financial performance of Islamic banking in Malaysia and Indonesia. The research objectives of this study are to investigate how the comparison of the effect of financial ratios, macroeconomics, and Shariah screening on the financial performance of Islamic banking in Malaysia and Indonesia and to identify which would be the most influential factor that affects the financial performance of Islamic banking in Malaysia and Indonesia. This study utilizes the secondary data collected from the annual financial reports of ten Malaysian Islamic banks and ten Indonesian Islamic banks from 2015 to 2020. This study categorized the explanatory variables into financial ratios, macroeconomics, and Shariah screening. The financial ratio factors include Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR); macroeconomics factors include inflation, Gross Domestic Product (GDP), and exchange rate, while Shariah screening factors include Islamic investment, Islamic income, and Profit-sharing ratio. In order to achieve the research objectives of this study, the researcher uses a panel data multiple linear regression model to test the effect of independent variables on dependent variables. Results have shown that for Malaysian Islamic banking’s performance, there are three variables significantly influence the financial performance of Malaysian Islamic banks: Capital Adequacy Ratio (CAR) of financial ratio factors, Gross Domestic Product (GDP) of the macroeconomic factors, and Profit-sharing of Shariah screening factors. In comparison to Indonesian Islamic banks, this study finds that seven independent variables have a significant impact to the financial performance of Islamic banks in Indonesia: Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) of financial ratio factors; Gross Domestic Product (GDP) and Exchange rate of the macroeconomic factors; and Islamic investment and Islamic income of Shariah screening factors.